Globalization and Protection of Employment - Justina A. V. Fischer; Frank Somogyi (ETH Zurich, KOF Swiss Economic Institute, 2009)
Unionists and politicians frequently claim that globalization lowers employment protection of workers. This paper tests this hypothesis in a panel of 28 OECD countries from 1985 to 2003, differentiating between three dimensions of globalization and two labor market segments. While overall globalization is shown to loosen protection of the regularly employed, it increases regulation in the segment of limited-term contracts. We find the economic one to drive deregulation for the regularly employed, but the social one to be responsible for the better protection of workers in atypical employment. We offer political economy arguments as explanations for these differential effects.
Keywords: C33; F15; F16; J81; J83; O57; 330; Globalization; international trade; integration; employment protection; labor standards; unions; cross-country analysis; panel data analysis; Globalisierung; Außenhandelsliberalisierung; Arbeitnehmerschutz; Arbeitsmarktflexibilität; Ungeschützte Beschäftigung; OECD-Staaten